Atomically Dispersed CoN3C1‐TeN1C3 Diatomic Sites Anchored in N‐Doped Carbon as Efficient Bifunctional Catalyst for Synergistic Electrocatalytic Hydrogen Evolution and Oxygen Reduction (Small 29/2022). Issue 29 (21st July 2022) - Wang, Minmin; Zheng, Xiuhui; Qin, Donglin; Li, Min; Sun, Kaian; Liu, Chuhao; Cheong, Weng‐Chon; Liu, Zhi; Chen, Yanju; Liu, Shoujie; Wang, Bin; Li, Yanpeng; et al.
Abstract : Bifunctional Catalysts In article number 2201974, Yunqi Liu, Xuan Yang, Xiang Feng, Yuan Pan, and co‐workers propose an encapsulation‐adsorption‐pyrolysis strategy for constructing Co‐Te diatomic sites with special CoN3 C1 ‐TeN1 C3 coordination structure anchored in N‐doped carbon, as efficient bifunctional catalysts for synergistic electrocatalytic hydrogen evolution and oxygen reduction. This work provides numerous opportunities for the rational design and artificial synthesis of diatomic sites catalysts for energy conversion.